Rapid progressing allele HLA-B35 Px restricted anti-HIV-1 CD8+ T cells recognize vestigial CTL epitopes. - Willberg, C; Garrison, K; Jones, R; Meiklejohn, D; Spotts, G; Liegler, T; Ostrowski, M; Karlsson, A; Hecht, F; Nixon, D (Public Library of Science, 2010)
BACKGROUND: The HLA-B*35-Px allele has been associated with rapid disease progression in HIV-1 infection, in contrast to the HLA-B*35-Py allele. METHODOLOGY/PRINCIPAL FINDINGS: Immune responses to two HLA-B*35 restricted HIV-1 specific CTL epitopes and their variants were followed longitudinally during early HIV-1 infection in 16 HLA-B*35+ individuals. Subjects expressing HLA-B*35-Px alleles showed no difference in response to the consensus epitopes compared to individuals with HLA-B*35-Py alleles. Surprisingly, all the HLA-B*35-Px+ individuals responded to epitope-variants even in the absence of a consensus response. Sequencing of the viral population revealed no evidence of variant virus in any of the individuals. CONCLUSIONS/SIGNIFICANCE: This demonstrates a novel phenomenon that distinguishes individuals with the HLA-B*35-Px rapid progressing allele and those with the HLA-B*35-Py slower progressing allele.